2010
DOI: 10.1111/j.1463-1326.2010.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial uncoupling protein 2 in pancreatic β‐cells

Abstract: Pancreatic β-cells have remarkable bioenergetics in which increased glucose supply upregulates the cytosolic ATP/ADP ratio and increases insulin secretion. This arrangement allows glucose-stimulated insulin secretion (GSIS) to be regulated by the coupling efficiency of oxidative phosphorylation. Uncoupling protein 2 (UCP2) modulates coupling efficiency and may regulate GSIS. Initial measurements of GSIS and glucose tolerance in Ucp2 −/− mice supported this model, but recent studies show confounding effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
(112 reference statements)
1
16
0
1
Order By: Relevance
“…1). On the contrary, the induction of UCP2 expression in β-cells has an adverse effect on hyperglycemia, because a reduced ATP:ADP ratio and ROS production together with increased release of lactate would inhibit insulin secretion (28)(29)(30)(31). Consistent with this explanation, we have found that replacement of Gly-268 with Ala in UCP2, a mutation associated with congenital hyperinsulinism (32), causes a marked decrease in the transport activity of UCP2 (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…1). On the contrary, the induction of UCP2 expression in β-cells has an adverse effect on hyperglycemia, because a reduced ATP:ADP ratio and ROS production together with increased release of lactate would inhibit insulin secretion (28)(29)(30)(31). Consistent with this explanation, we have found that replacement of Gly-268 with Ala in UCP2, a mutation associated with congenital hyperinsulinism (32), causes a marked decrease in the transport activity of UCP2 (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…While UCP2 has a wide tissue distribution (60), it is expressed at very low levels, comparable to that of most metabolite transporters. The UCP2 content of mitochondria isolated from INS-1E cells depended on the prior nutritional status of the cells, and varied from 2.7 ng/mg mitochondrial protein in the absence of both fetal calf serum and glutamine to 14.5 ng/mg mitochondrial protein in full culture medium containing 20 mM glucose, responding with a half-life of ϳ1 h (31,63). Even this latter figure is Ͻ0.1% of the content of UCP1 in cold-adapted brown fat.…”
Section: H the Contentious Role Of Ucp2mentioning
confidence: 99%
“…Given their effects on mitochondrial bioenergetics, uncoupling proteins have been implicated in the physiology and pathophysiology of pancreatic β-cells. 5,31,32 Our simulation on the basis of model showed (see Fig. 4 from ref. 17) that at a constant glucose level increased uncoupling protein activity leads to decreases in Ψ m and [Ca 2+ ] c .…”
Section: This Is Because the Nad(p)h/nad(p)mentioning
confidence: 82%
“…This effect of increased activity of uncoupling proteins has been described experimentally. 5,32 However, our simulation also shows a novel aspect of this problem: an ability of uncoupling proteins (and other uncoupling agents) to shift the glucose dependence of the ATP/ADP ] c at different leak activity. To simulate increased leak activity we magnified the proton leak rate two-fold.…”
Section: This Is Because the Nad(p)h/nad(p)mentioning
confidence: 87%